Study of the structure of organo-modified palygorskite - Zhdanyuk, Nataliya (Technology audit and production reserves, 2017)
The object of research is a natural silicate with a layer-band structure - palygorskite of the Cherkasy deposit (Ukraine). One of the problematic areas in the technology of sorption purification of aqueous media using palygorskite is the absence of kinship of the mineral in anionic forms of pollution. Therefore, its use as a sorbent to extract ions Cr(VI), U(VI), As(V), which are in aqueous media in anionic forms, is ineffective. In the course of the study, XRD methods, thermal analysis and a spectrophotometric method are used to study the sorption properties of synthesized materials. The structures of palygorskite and modified samples are studied using -ray diffraction analysis (XRD). After treatment with Na-PG, changes in its crystal structure are observed. There is a shift of the peaks toward large angles 2θ. Comparison of the diffractograms OPG-1 and OPG-2 allows to conclude that the reflection with the same indices is not relatively displaced, but their intensity is different. In OPG-2, the intensity of most peaks is higher. The thermal properties of palygorskite and the resulting composites are studied. According to the results of sorption studies, it is established that palygorskite modified at a ratio of CEC/surfactant=1 can remove up to 97.8 % of Cr(VI) ions. This is 16.2 times more than adsorbing natural palygorskite. As a result of studies of the Cr(VI) adsorption on Na-PG, OPG-1 and OPG-2, it has been shown that modifying the palygorskite surface by GDTMA can increase the adsorption of Cr(VI) from 0.45 mg/g and 9.2 mg/g, respectively. And for the initial concentration of the solution is 100 mg/l to 4.2 and 12.3 mg/l, respectively. Increasing the volume of practical use of natural silicate materials contributes to a comprehensive solution of environmental issues, resource saving and technology for the production of sorbents for the extraction of anionic forms of Cr(VI) and U(VI) from aqueous solutions.